Ethical Consumption and New Business Models in the Food Industry. Evidence from the Eataly Case - Sebastiani, Roberta; Montagnini, Francesca; Dalli, Daniele (2013)
Individual and collective ethical stances regarding ethical consumption and related outcomes are usually seen as both a form of concern about extant market offerings and as opportunities to develop new offerings. In this sense, demand and supply are traditionally portrayed as interacting dialectically on the basis of extant business models. In general, this perspective implicitly assumes the juxtaposition of demand side ethical stances and supply side corporate initiatives. The Eataly story describes, however, a different approach to market transformation; in this case a company and a social movement (Slow Food) have negotiated and collaborated prior to initiating a new business model. This collaboration process and its outcomes are described, focusing specifically on ordinary Eataly customers’ and Slow Food members’ reactions. Given that Eataly can be regarded as a case of mainstreaming, ordinary customers seem satisfied with the new offering and the Slow Food support for the initiative; the more purist members of the Slow Food movement had critical concerns, however, as happened in similar conditions, according to literature, with regard to Fair Trade. The Slow Food endorsement of the new venture has also been observed from the attitude–behaviour gap perspective, as it contributed to addressing the factors affecting the gap between attitudes and actual behaviours. Extensive qualitative data were collected and analysed over a 3-year period. The main study implications refer to the ways in which companies and social movements could interact to co-design new business models, as well as outlining consumers’ attitudes and behaviours towards such new offerings.
Keywords: Social Movements; Slow Food; Participative business model; Ethical consumption; Case study; Attitude–behaviour gap